Motion Planning for Omnidirectional Wheeled Mobile Robot by Potential Field Method - Weihao Li; Chenguang Yang; Yiming Jiang; Xiaofeng Liu; Chun-Yi Su (Journal of Advanced Transportation)
In this paper, potential field method has been used to navigate a three omnidirectional wheels’ mobile robot and to avoid obstacles. The potential field method is used to overcome the local minima problem and the goals nonreachable with obstacles nearby (GNRON) problem. For further consideration, model predictive control (MPC) has been used to incorporate motion constraints and make the velocity more realistic and flexible. The proposed method is employed based on the kinematic model and dynamics model of the mobile robot in this paper. To show the performance of proposed control scheme, simulation studies have been carried to perform the motion process of mobile robot in specific workplace.